2022
DOI: 10.1038/s41380-022-01751-z
|View full text |Cite
|
Sign up to set email alerts
|

Shared genetic architecture between schizophrenia and subcortical brain volumes implicates early neurodevelopmental processes and brain development in childhood

Abstract: Patients with schizophrenia have consistently shown brain volumetric abnormalities, implicating both etiological and pathological processes. However, the genetic relationship between schizophrenia and brain volumetric abnormalities remains poorly understood. Here, we applied novel statistical genetic approaches (MiXeR and conjunctional false discovery rate analysis) to investigate genetic overlap with mixed effect directions using independent genome-wide association studies of schizophrenia (n=130,644) and bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 61 publications
2
11
0
Order By: Relevance
“…Interestingly, Weiqiu et al, in their study, identified a ramarkable shared genetic architecture between schizophrenia and subcortical volumes, in particular, 54% for schizophrenia. Furthermore, this study also found that shared genetic loci reached the expression peak at the prenatal age, consistent with our assumption that the pathogenesis of schizophrenia, especially the one involving immunology, could start around the perinatal period, either triggered or precipitated by intrauterine infection or inflammation involving CRP [34].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, Weiqiu et al, in their study, identified a ramarkable shared genetic architecture between schizophrenia and subcortical volumes, in particular, 54% for schizophrenia. Furthermore, this study also found that shared genetic loci reached the expression peak at the prenatal age, consistent with our assumption that the pathogenesis of schizophrenia, especially the one involving immunology, could start around the perinatal period, either triggered or precipitated by intrauterine infection or inflammation involving CRP [34].…”
Section: Discussionsupporting
confidence: 90%
“…Our results imply that the change in the CRP level caused by SCZ leads to a misaligned growth trajectory of WMV between cerebral and cerebellar areas. Our study, for the first time, established the causal link from CRP to the pallidum’s GMV changes which played a substantial role in various mental functions [32, 33]. Interestingly, Weiqiu et al, in their study, identified a ramarkable shared genetic architecture between schizophrenia and subcortical volumes, in particular, 54% for schizophrenia.…”
Section: Discussionmentioning
confidence: 54%
“…We then systematically quantified genetic architecture beyond genome‐wide genetic correlations between PD and BSPs by using MiXeR and discovered a modest genetic overlap between PD and SA, TH, caudate volume, hippocampus volume, nucleus accumbens volume, putamen volume, and thalamus volume, respectively, which showed patterns of mixed effect directions concealed by estimates of genome‐wide genetic correlations. However, the lower degree of overlap between PD and many brain MRI measures, compared with that reported for psychiatric diagnoses, 29,40 could potentially be caused by the intricate interplay between genetic and environmental factors influencing PD. The shared genetic associations were found by conjFDR at individual variant and locus levels, and Q‐Q plots indicated significant polygenic overlap between PD and SA, TH, ICV, hippocampus volume, and putamen volume, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…This locus harbors a inversion polymorphism and includes PLEKHM1, MAPT, KANSL1 and CRHR1. CRHR1 encodes the main receptor of corticotrophin-releasing hormone and has recently been highlighted in a study of shared genetic effects on schizophrenia and subcortical volumes [54]. MAPT encodes microtubule-associated protein tau, which is known for its role in axonal transport and neurite outgrowth and has previously been associated with schizophrenia and structural MRI metrics [7].…”
Section: Chromosomal Clusters Of Genes Pleiotropically Associated Wit...mentioning
confidence: 99%